Fabrication and characterization of biocomposite pellets from cassava starch and oil palm empty fruit bunch fibers - Yora Faramitha; Firda Dimawarnita; Adi Cifriadi; Happy Widiastuti; Tjahjono Herawan (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Oil palm empty fruit bunches (OPEFB) are lignocellulosic biomass that can be used to produce a biocomposite as an alternative to substitute non-renewable materials, such as plastic. Generally, the production of biocomposites uses OPEFB, which has been processed into cellulose, microcrystalline cellulose, or nanocellulose and is mixed with starch. However, the OPEFB pretreatment into various types of cellulose requires a long process and many chemicals. The OPEFB pretreatment with less process, such as cutting to shorter fibers and without chemicals, was expected to shorten the process. This study aims to produce and evaluate the characteristics of biocomposite pellets from a combination of cassava starch and OPEFB fibers. Short OPEFB fibers (3-5 mm) with varying concentrations of 0, 5, 10, 15, and 20% were added to the cassava starch before mixing with other materials. The twin screw extruder used to produce biocomposite pellets was set at six temperature zones ranging from 85-140 °C and the screw speed in the range of 160-190 rpm. The results show that higher concentrations of OPEFB fibers produced darker pellets, which tended to be greyish. The biocomposite pellets had densities of 1.322-1.417 g cm-3. SEM results show some agglomerations on the surface of starch-OPEFB fibers biocomposite pellets. The water solubility of biocomposite pellets ranged from 32.97 – 36.44%. In conclusion, biocomposite pellets could be produced from a mixture of cassava starch and OPEFB fibers up to 20%. In its application for rigid packaging production, the biocomposite pellets’ performance could be improved by mixing them with recycled polypropylene.